2008
DOI: 10.2190/il.16.4.c
|View full text |Cite
|
Sign up to set email alerts
|

Journeying with Morrie: Challenging Notions of Professional Delivery of Spiritual Care at the End of Life

Abstract: The spiritual welfare of dying people has in recent years moved from the domain of religion to become the concern of health care professionals, particularly as part of the ideal of holism that underpins palliative care. Professional delivery of spiritual care incorporates the features of assessment, control and treatment which may involve varying degrees of intrusion into the patient's deeply personal inner self. Using a case study approach, this article explores meanings of spirituality and understandings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…91 The author of a case study of a man with multiple myeloma contested that measuring spiritual needs is a form of depersonalization and concluded that spiritual needs were substantially situational and biographic and could only be met by someone with shared memories and in the context of long-standing and valued relationships, something, therefore, not possible for health care professionals. 94…”
Section: Primary Findings Of Studiesmentioning
confidence: 99%
“…91 The author of a case study of a man with multiple myeloma contested that measuring spiritual needs is a form of depersonalization and concluded that spiritual needs were substantially situational and biographic and could only be met by someone with shared memories and in the context of long-standing and valued relationships, something, therefore, not possible for health care professionals. 94…”
Section: Primary Findings Of Studiesmentioning
confidence: 99%
“…New ways to both assess and address spiritual concerns as part of overall well-being are being developed by health care practitioners as part of a package of support for people with critical and terminal illness (Randall & Downie, 2006;Watts, 2008a). For this support to be meaningful, however, it is necessary to determine which dimensions of spirituality are relevant and the ways in which the human spirit can be celebrated in the face of life-threatening illness (Cobb & Legood, 2008).…”
Section: Introductionmentioning
confidence: 99%